O princípio da subsidiariedade e o terceiro setor: desafios e potencialidades de políticas públicas em âmbito local - Gallas, Mirelle (2021)
This Dissertation is part of the Research Line Social Relations and Dimensions of Power. The study seeks to analyze whether the Subsidiarity Principle is foundation to support Local Government actions to carry out services public policies and public policies that are consistent with social rights, through Third Sector. To this end, the three proposed chapters analyzed the conception of social rights in the 1988 Federal Constitution and their implementation through services public policies and public policies, harmed due to the welfare state crisis. The conception of the Third Sector will be seen, as one of the elements of the reform management of the State, its composition by non-state public institutions, and its current legitimizing regulation, in order to assess whether or not there is a distortion of the conception of actions under state competence. Regarding the Principle of Subsidiarity, implicit in the legal system, discusses its origin in Christian social doctrine and constituent aspects, such as the distribution of competences and decentralization, consistent with the constitution of the Brazilian Federation. In that In the meantime, considering the Municipality as an autonomous federative entity, if it has the power established location, capable of carrying out numerous actions, according to the distribution of powers set out in the Federal Constitution. Finally, the assessment of the Power Location and effectiveness of its actions permeates the democratic conception of popular participation, through countless social actors capable of legitimizing management local, through proposals, participation in the identification of more close to where people live, in cities. The insertion of the culture of participation in decision-making processes, through mechanisms highlighted in the legal norms, currently measured as part of citizenship inseparable from modern democratic conception, not imitated by suffrage. It is assessed whether such mechanisms can be the future option for citizenship education so that choices can be adapted to implementation of social rights and good local public management, through examples of current mechanisms.